2019
DOI: 10.33846/sf10303
|View full text |Cite
|
Sign up to set email alerts
|

Model Keperawatan Keluarga Santun Lansia dalam Upaya Peningkatan Kualitas Asuhan Keluarga pada Lansia: A Literature Review

Abstract: Family is the closest person to the elder person who has an important role in caring for elder person. The purpose of this study is to provide an overview of the cordial older family nursing model in an effort to improve the quality of family care in elder person. The study approach was the study of literature with expert agreement. The search method for library resources was done online, which uses databases such as Science Direct, Scopus, Sage, Pubmed and ProQuest. The keywords used were "elder mistreatemnt"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Older adults not accompanied by their children tend to have an increased knowledge and skills that is not significant to their ability to manage their pain. The results of previous research also explained that family support can change the behavior of older adults to become more health-conscious (Rekawati, 2014). Based on this, the importance of family support to successfully implement joint pain management can be interpreted.…”
Section: Discussionmentioning
confidence: 80%
“…Older adults not accompanied by their children tend to have an increased knowledge and skills that is not significant to their ability to manage their pain. The results of previous research also explained that family support can change the behavior of older adults to become more health-conscious (Rekawati, 2014). Based on this, the importance of family support to successfully implement joint pain management can be interpreted.…”
Section: Discussionmentioning
confidence: 80%
“…Studies show that about two-thirds of the world's elderly population lives in developing countries, and it is argued that shortly, aging will become one of the most important social and welfare challenges in developing countries [1]. Therefore, the health and well-being of older people have become a major focus of attention in health policies worldwide [2], [3]. Fulfilling the health and well-being of older people cannot be separated from the support system provided by the family.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, the role of family nurses is often ignored and needs to be recognized more by medical authorities and society. Therefore, it is necessary to research to identify the implementation of family care models and to evaluate the effectiveness of these models in improving the health and well-being of elderly people in society [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nursing care for older people may involve their family through training, through giving a positive perception to family members who take care of them, and through counseling. 6 Receiving support from a family by who are enabled to provide health information influences the behavior of the older person who is receiving treatment for hypertension. 7 Another study also showed a positive correlation between self-management and family support in treating elderly people with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%